Mulberry Leaves (Morus alba) for Diabetes Mellitus: Acute Toxicity Test in Male Wistar Rats - Rena Nurita; Anisa Vitriana; Isni Maulina Sukmara; Nurul Utami; Maryam Maryam; Fathul Huda; Vycke Yunivita (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Diabetes mellitus (DM) is a chronic disease which becoming health community problem in the world. DM patients can be treated by antidiabetic drugs throughout their lifetime. Therefore, to alleviate the concern for the side e ect, it is important to have an alternative therapy which has same e ect but less side e ect. One of alternative therapies which has been known for a long time ago is Mulberry leaves (Morus alba). For something to be clinically used as an alternative therapy, e ective and lethal dose should be known. Here we tried to discover the lethal dose (LD50) and the liver morphological changes, using the e ective dose that had been known from previous study. In our experiment, we used Morus alba leaves infusion and 25 male Wistar rats. These rats were divided into 1 control group and 4 groups treatment dosage, 0.3, 3, 30, and 300 grams/kg bodyweight. We observed the mortality in 7 days and examined the liver morphological changes. From this study, we conclude that 300 grams/ kg bodyweight or 48 grams/kg bodyweigtht in human was pseudolethal dose in male Wistar rats. We did not found any signi cant liver morphological changes. Therefore, we can categorize Morus alba as a harmless alternative therapy. Key words: Alternative therapy, diabetes mellitus, liver morphological changes, lethal dose, Morus alba.